Factorial analysis of trace elements of Tamarindus indica with reference to Bela ophiolite - Hamza, Salma; Naseem, Shahid; Ul-Huda, syed Nawaz; Bashir, Erum; Burke, Farkhunda; Sheikh, Shamim (International Journal of Basic and Applied Sciences, 2014)
A study of ophiolitic rocks, soils, twigs and fruits of Tamarindus indica have been carried out to evaluate elemental relationship. Soil of the study area revealed concentration of trace elements acquired from the bedrock. Its average abundance (mg/kg) in the soil was Mn (30), Fe (28), Pb (5.12), Cr (4.7), Ni (3.12), Cu (2.66), Zn (1.02), Co (0.97) and Cd (0.49). Fruit pulp presented: Fe (16.0), Cr (5.57), Zn (3.75), Mn (2.99), Cu (2.05), Co (0.92) and Ni (0.24). Twigs of T. indica showed Fe>Zn>Mn>Cu>Ni>Cr>Pb>Co>Cd trend of concentration. Elemental composition of rock-soil-twig-fruit of T. indica demonstrated similarities in the distribution pattern, reflecting common association between them. Correlation matrix (CM) and principal component analysis (PCA) revealed that elemental distribution of T. indica is influenced by the composition of rocks and soils of the study area. Keywords: PCA; Rock-Soil-Twig-Fruit Relation; Element Distribution; Geochemistry; Balochistan.